O.M. Kovalevsky's materials at the Department of Manuscripts and Documents of the Institute of Oriental Manuscripts of the Russian Academy of Sciences - N.S. Yakhontova (Ученые записки Казанского университета: Серия Гуманитарные науки)
An attempt was made to identify the manuscripts and xylographs from the private library of O.M. Kovalevsky (Józef Kowalewski) in the Kazan Theological Academy Collection. The Kazan Theological Academy Collection (about 500 items) was created in 1927 as part of the Mongolian Foundation at the Department of Manuscripts and Documents of the Institute of Oriental Manuscripts of the Russian Academy of Sciences. It was revealed that several dozens of items originally belonging to the private library of O.M. Kovalevsky are stored in this collection. According to the A.G. Sazykin’s catalogue, this collection involves more than 100 letters addressed to O.M. Kovalevsky, i.e., from his archive. However, there is enough evidence to claim that at least 38 more items (mainly Beijing and earliest Buryat xylographs) were once in his own possession. This conclusion is based on the identification of O.M. Kovalevskiy’s neat handwriting distinguished in these texts. He wrote inscriptions in different languages: Polish, Russian, Mongolian, French, etc. on the covers, made notes inside the texts, copied whole texts and made extracts. These facts allow us to attribute all the texts bearing such marks as a part of the personal library of O.M. Kovalevsky. The obtained results are important for establishing the history of materials of the Kazan Theological Academy Collection, on the one hand, and the history of life and scientific work of O.M. Kovalevsky, on the other hand.